Le monastere Saint-Pierre d'Osor (ile de Cres): sixieme campagne d'etudes archeologiques - Jurković, Miljenko (Array, 2012)
In the 2011 campaign the southern and central apse, as well as the southern nave of the abbey church of St peter were excavated. The primary analysis of the eastern part of the Venetian town wall was undertaken as well. The geophysical survey of the wetern and south-eastern parts of the coplex has equally been continued. The initial results allow us to present a phasing of the early Romanesque church, possibly preceded by two earlier churches.